The Nemp1–Nesprin complex mediates cellular responses to matrix mechanics - Abira Ganguly; Hannah Zmuda; Javier Abello; Danielle Illy; Christopher Walter; Yonit Tsatskis; Nattapon Thanintorn; Ying Zhang; Bilal Ahmad Hakim; Didier Hodzic; Amber N. Stratman; Andrea Jurisicova; et al. (Proceedings of the National Academy of Sciences, 2026)
Nuclear Envelope Membrane Protein 1 (NEMP1) is crucial for metazoan fertility; loss of Nemp1 causes death of primordial oocytes that reside in the mechanically challenging ovarian cortex. Here, we show that softening the ovary rescues oocyte loss and restores fertility in N emp1 knockout (KO) mice. In cell culture, NEMP1 depletion on stiff substrates leads to death, while cells remain viable on soft substrates. We further show that NEMP1 regulates YAP nuclear translocation, essential for mechanotransduction. Mechanistically, Nemp1-depleted cells on stiff substrates or subjected to stretching exhibit reduced nuclear YAP localization, and expressing nuclear YAP5SA restores cell viability. Loss of NEMP1 disrupts actin organization. Inducing actin polymerization partially rescues nuclear YAP, indicating a role for F-actin in NEMP1 mediated mechanotransduction. NEMP1 forms a complex with NESPRIN’s Klarsicht, Anchorage (ANC)-1, Syne Homology (KASH) domain, strengthening the actin cytoskeleton to withstand mechanical forces, independent of SUN proteins. Thus, the Nemp1–Nesprin complex supports a mechanosensitive pathway parallel to the LINC complex, enabling cellular response to mechanical stress in vitro and in vivo.